Existence and Uniqueness of the Solution for Hilfer Neural Networks with Delays (Journal of Nonlinear Modeling and Analysis, 2024)
This paper mainly concerns with a class of nonlinear Hilfer fractional neutral recurrent neural networks with time varying delays. The existence and uniqueness of solutions in the space of weighted continuous functionsare established by Banach’s contraction principle. Finally, an example is provided to illustrate the application of the obtained results.
Keywords: Hilfer fractional differential equation; existence and uniqueness; weighted space of continuous functions; fixed point theory.